PEMETAAN LEMBAGA KERJASAMA REGIONAL DI JAWA TENGAH - Warsono, Hardi (JURNAL ILMU SOSIAL, 2007)
The research aims to elaborate on the various froms of regionalization and the regional cooperation institutions in Central Java. The focus of this reseach, cooperation between neightboring regions (subsequently addressed as regional cooperation), is one of the numerous forms of inter-regional cooperation. Other forms include cooperation between non-neighboring regions, multilateral regional cooperation and so forth. This reseach was able to map the existence of various regionalization and regional cooperation institutions. There are eight (8) regions initiated by the province, which werw know asa Priority Territory (Based on Provincial Regulation number 21 of te year 2003, About aewa Zoning). Constructing the future model of institution, the objectives of the cooperation to be involved and be oriented towards a comprehencive program, scope of the cooperation should be wide - ranging, i,e include economic and non economic cooperation (public service). Format of the institution should be developed gradually from sectoral accepted principles and funds should be shared wqually and fairly among all participating members.